Involvement of hrpX and hrpG in the Virulence of Acidovorax citrulli Strain Aac5, Causal Agent of Bacterial Fruit Blotch in Cucurbits - Zhang, Xiaoxiao; Zhao, Mei; Yan, Jianpei; Yang, Linlin; Yang, Yuwen; Guan, Wei; Walcott, Ron; Zhao, Tingchang (Frontiers in Microbiology, 2018)
Acidovorax citrulli causes bacterial fruit blotch, a disease that poses a global threat to watermelon and melon production. Despite its economic importance, relatively little is known about the molecular mechanisms of pathogenicity and virulence of A. citrulli. Like other plant-pathogenic bacteria, A. citrulli relies on a type III secretion system (T3SS) for pathogenicity. On the basis of sequence and operon arrangement analyses, A. citrulli was found to have a class II hrp gene cluster similar to those of Xanthomonas and Ralstonia spp. In the class II hrp cluster, hrpG and hrpX play key roles in the regulation of T3SS effectors. However, little is known about the regulation of the T3SS in A. citrulli. This study aimed to investigate the roles of hrpG and hrpX in A. citrulli pathogenicity. We found that hrpG or hrpX deletion mutants of the A. citrulli group II strain Aac5 had reduced pathogenicity on watermelon seedlings, failed to induce a hypersensitive response in tobacco, and elicited higher levels of reactive oxygen species in Nicotiana benthamiana than the wild-type strain. Additionally, we demonstrated that HrpG activates HrpX in A. citrulli. Moreover, transcription and translation of the type 3-secreted effector (T3E) gene Aac5_2166 were suppressed in hrpG and hrpX mutants. Notably, hrpG and hrpX appeared to modulate biofilm formation. These results suggest that hrpG and hrpX are essential for pathogenicity, regulation of T3Es, and biofilm formation in A. citrulli.